Perencanaan Peningkatan Jembatan Kayu di Jalan Minggu Gembira Desa Sungai Kinjil Pesisir Kecamatan Benua Kayong Kabupaten Ketapang - Kamil, Firmanilah; Karlina, Vevie; Efendi, Uti Rustam (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
The condition of the wooden bridge located on Jalan Minggu Gembira, Sungai Kinjil Pesisir Village is not suitable for use. The bridge is part of the upper structure that moves easily when there is a load passing or passing over the bridge and the bridge bridge does not have a backrest pole, and retaining walls due to this condition the activities of farmers and local residents are hampered. Therefore it is necessary to plan for the improvement of the wooden bridge. This bridge connects settlements with other public facilities. In addition, the bridge with a width of 3 m with a span of 6 m also serves to cross agricultural products. Given the importance of the bridge function in the area, it is necessary to prepare a wooden bridge improvement plan. The purpose of this study is to find out the drawing plan and how much the Budget Plan Cost (RAB) is on the planning of the wooden bridge improvement. Researchers used data collection methods in the form of field observations and data collection of the Ketapang Regency unit price list of materials and wages in 2023 from PUPR to make RAB. After making the drawing plan and analyzing the RAB calculation, it was found that the total cost required in planning the improvement of the wooden bridge on Jalan Minggu Gembira, Sungai Kinjil Pesisir Village, Benua Kayong District, Ketapang Regency was found to be Rp. 71,160,785.